Membongkar Supersemar : dari CIA hingga kudeta merangkak melawan Bung Karno / Baskara T. Wardaya; penyunting, Islah Gusmian, JF Tualaka - BASKARA T. WARDAYA; ISLAH GUSMIAN; TUALAKA, JF (Jogja Bangkit Publisher, 2017)
xxx, 190 hlm. : ilus. ; 23 cm.